The Mishnah in contemporary perspective. - Avery-Peck, Alan Jeffery, (1953- ...); Neusner, Jacob, 1932- (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2002)
The authors of the studies on the Mishnah collected in the present volumes represent the best of contemporary scholarship on that document. In the past thirty years, the Mishnah seen as a document on its own terms has taken its place as a principal focus in the academic study of religion and of Judaism. Many university scholars have participated in the contemporary revolution in the description, analysis, and interpretation of the Mishnah. Nearly all the publishing scholars of the academy (as distinct from the yeshiva or rabbinical seminary) who are now at work are represented in this project, ultimately planned for three volumes. In this and the companion volumes, the editors place on display a broad selection of approaches to the study of the Mishnah in the contemporary academy. What they prove in diverse ways is that the Mishnah defines the critical focus of the study of Judaism. It is a document that rewards study in the academic humanities. Because many viewpoints register here, this is the most representative selection of contemporary Mishnah-study available in any state-of-the-question-collection in a Western language.